Strategi Perguruan Tinggi Kemaritiman Menciptakan Wirausaha Muda Melalui Pendidikan Kewirausahaan - Ari Ani Dyah Setyoningrum (PPPM Polimarin, 2023)
Entrepreneurship is a pillar of the state in creating jobs and improving the community's economy. Colleges are obliged to provide knowledge that is useful in life, including knowledge in entrepreneurship. The purpose of providing entrepreneurship education is to motivate students to become entrepreneurs. The results of previous research indicated that there was an influence of entrepreneurship education in students' perceptions, interests and competencies to become entrepreneurs. But in reality, entrepreneurship education does not directly make the graduates dare to open a business. The aim of this study is to analyze the strategy of maritime colleges through entrepreneurship education in growing young entrepreneurs. The research method used is qualitative. Data was collected by interviews and observation. Based on the results, it can be concluded that maritime colleges have included entrepreneurship education in their teaching curriculum with 2 credits. This is a good strategy to provide students with the knowledge to become entrepreneurs. However, the courses is still taught in classical and theoretical learning. Meanwhile, entrepreneurial practices are still limited to making business plan. So there is a need for a follow-up program to be able to realize entrepreneurial graduates, like entrepreneurship center on campus, developing student entrepreneurship, increasing independent entrepreneurship, and providing student venture capital.